2011
DOI: 10.1021/es202827g
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbon Residues in Human Milk, Placenta, and Umbilical Cord Blood in Beijing, China

Abstract: This paper provides the results of an investigation on dietary intakes and internal doses of polycyclic aromatic hydrocarbons (PAHs) for nonsmoking women from Beijing, China. Concentrations of PAHs were measured by gas chromatography/mass spectrometry (GC/MS) for human milk, placenta, and umbilical cord blood samples from 40 nonsmoking women and for 144 composite food samples covering major food categories. Information on food consumption and estimated ingestion doses of PAHs by the cohort was also collected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(43 citation statements)
references
References 38 publications
2
37
4
Order By: Relevance
“…As far as we know, there is no study that has reported plasma levels of PAHs in dogs, and we can only compare the results with other studies in humans. Thus, the levels found in human plasma are comparable to those found in cord blood in Hong Kong in 2005 (1158 ng/g lw) (Tsang et al 2011) and in China in 2011 (1370 ng/g lw) (Yu et al 2011), but much lower than those found in maternal and cord blood in Texas, USA (5.5 and 12.8 ng/g ww) (Sexton et al 2011). In any case, it should be noted that these comparisons are not totally reliable since in these papers a different number of compounds were included, with 15 analytes in the works of Hong Kong and China and 50 individual PAHs in the work of Texas.…”
Section: Concentrations Of Pahs In Dog and Human Plasmasupporting
confidence: 64%
See 1 more Smart Citation
“…As far as we know, there is no study that has reported plasma levels of PAHs in dogs, and we can only compare the results with other studies in humans. Thus, the levels found in human plasma are comparable to those found in cord blood in Hong Kong in 2005 (1158 ng/g lw) (Tsang et al 2011) and in China in 2011 (1370 ng/g lw) (Yu et al 2011), but much lower than those found in maternal and cord blood in Texas, USA (5.5 and 12.8 ng/g ww) (Sexton et al 2011). In any case, it should be noted that these comparisons are not totally reliable since in these papers a different number of compounds were included, with 15 analytes in the works of Hong Kong and China and 50 individual PAHs in the work of Texas.…”
Section: Concentrations Of Pahs In Dog and Human Plasmasupporting
confidence: 64%
“…In any case, it should be noted that these comparisons are not totally reliable since in these papers a different number of compounds were included, with 15 analytes in the works of Hong Kong and China and 50 individual PAHs in the work of Texas. However, if we compare only the values of the most toxic PAHs (PAH7) with those reported in the literature, we found that levels of this study were much lower than those described in China (Yu et al 2011;Guo et al 2012;Song et al 2013) and Hong Kong (Tsang et al 2011).…”
Section: Concentrations Of Pahs In Dog and Human Plasmacontrasting
confidence: 56%
“…The annual-average concentrations of the sum of the 15 EPA priority-controlled PAHs (SPAH 15 ), excluding naphthalene, in Beijing urban air is reported to be about 206 ng m À3 , with a BAP concentration of about 6 ng m À3 , which is considerably higher than the national standard (1 ng/m 3 ) (Li et al 2014). Yu et al (2011) reported that the median concentrations of SPAH 15 in human milk, placenta, and umbilical cord blood for the Beijing population were 278, 819, and 1372 ng g À1 of fat, respectively, which were higher by almost an order of magnitude than corresponding levels in Japan and the United States, which may be caused by the higher PAH concentrations of various food types in the local area (Yu et al, 2011). An epidemiological investigation showed that there were 40,307 new cases of malignant tumors in Beijing in 2012 (Beijing Municipal Government, 2014), which was twice the level of 10 years ago.…”
Section: Introductionmentioning
confidence: 98%
“…Regarding dietary exposure, the difference in PAH bio-accessibility among food types is becoming a concern. It has been reported that the PAH concentrations vary among food types and according to PAH molecular weight (Xia et al, 2010;Yu et al, 2011). For these reasons, a systematic and detailed survey of the relative contributions of diet and inhalation is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Also, sufficient evidence exists of a link between the prenatal exposure to mixtures of carcinogenic PAHs and intrauterine growth restriction in humans (10). Study of nonsmoking women from Beijing proved detectable concentrations of PAHs in breast milk, placenta and umbilical cord blood (18).…”
Section: Introductionmentioning
confidence: 99%